RANCANG BANGUN SISTEM INFORMASI BEASISWA MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) (STUDI KASUS : MASS TEBUIRENG) - Sawung Sajiyanto , Aldi; Heru Mujianto , Ahmad (Inovate, 2024)
Madrasah Aliyah Salafiyah Syafi'iyah (MASS) Tebuireng, one of the formal educational institutions under the auspices of the Hasyim Asy'ari Foundation, also provides opportunities for students who excel to get scholarships and provide assistance to students who come from underprivileged families. Students who will become potential scholarship recipients include students who have parallel rankings, are currently or have memorized the Al-Qur'an, have academic and non-academic achievements, as well as students whose parents are underprivileged. There needs to be a method to build an SPK, one of which is the Simple Multi Attribute Rating Technique (SMART) method. This method is a method in making decisions to handle multi-criteria problems based on calculating the weight of the criteria for each alternative, so as to obtain the best results. The research results have resulted in a decision support system that can assist the MASS Tebuireng leadership in determining and selecting scholarship recipients. Keywords: Scholarship, SMART, Decision Support System.